Czy renesans monarchii absolutnej? Zmianyw Konstytucji Księstwa Lichtensteinu z 2003 roku. - Łukaszewski, Marcin (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In 2003 citizens of Liechtenstein adopted a package of amendments to the Constitution which allowed for a substantial strengthening of the monarch’s power. These changes have since been severely criticized by the Council of Europe, with concerns as to the possible retreat from a constitutional monarchy leading to the possible renaissance of absolute monarchy. This question is answered in this article, which further proves that the concerns raised by the Council of Europe are unjustified.